Determinants of transplantation success with cryopreserved ovarian tissue: data from 196 women of the FertiPROTEKT network - Lotz, Laura; Bender-Liebenthron, J.; Dittrich, Ralf; Häberle, Lothar; Beckmann, Matthias; Germeyer, A.; Korell, M.; Saenger, N.; Kruessel, J. S.; Von Wolff, Michael (Human Reproduction, 2022)
STUDY QUESTION What are the pregnancy and live birth rates for ovarian tissue transplantation and which factors are associated with the success rate? SUMMARY ANSWER Pregnancy and live birth rates per transplanted woman are 32.7% and 26.5% and success rate is associated with female age and first versus repeated transplantation. WHAT IS KNOWN ALREADY Live birth rates after ovarian tissue transplantations have been reported to be between around 24% and 41% per patient. Success rates seem to be negatively associated with increasing female age at the time of tissue cryopreservation and with pelvic radiation. Success rates are apparently not reduced after overnight transportation of ovarian tissue before freezing. STUDY DESIGN, SIZE, DURATION Registry analysis of 244 transplantations in 196 women, performed by 26 FertiPROTEKT network centres from 2007 to 2019 with follow-up till December 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS Orthotopic ovarian tissue transplantations were performed in 196 women, 191 with previous malignant and 5 with previous non-malignant diseases. Size of transplanting centres varied between 1 and 100 transplantations per centre (median: 2). Factors possibly associated with success rate such as female age, first and repeated transplantation, experience of the transplanting centre and overnight transportation of the ovarian tissue before freezing were analysed. MAIN RESULTS AND THE ROLE OF CHANCE Average age of all 196 transplanted women was 31.3 years (SD 5.2; range 17-44) at the time of cryopreservation of tissue and 35.9 years (SD 4.8; range 23-47) at the time of transplantation. Pregnancy rate was 30.6% (95% CI, 24.2-37.6%) per first transplantation and 32.7% (95% CI, 26.1-39.7%) per patient. Pregnancy rate was higher after first transplantation (30.6% (95% CI, 24.2-37.6%)) compared to second and subsequent transplantations (11.8% (95% CI, 3.3-27.5%)). Live birth rate per first transplantation was 25.0% (95% CI, 19.1-31.7%) and per patient 26.5% (95% CI, 20.5-33.3%). Success rate decreased with increasing age at the time of ovarian tissue freezing. Live birth rate was 28.2% (95% CI, 20.9-36.3%) in women <35 years and 16.7% (95% CI, 7.9-29.3%) in women >35 years. Pregnancy rates after first transplantation were higher in centres who had performed >= 10 transplantations (35.1%) compared to centres with <10 transplantation (25.4%) (P = 0.12). Corresponding live birth rates were 27.0% and 18.6%. Success rates were not different in women with and without overnight transportation of tissue before cryopreservation. LIMITATIONS, REASONS FOR CAUTION The data were drawn from a registry analysis. Data such as ovarian reserve and premature ovarian insufficiency were not available for all women. Data might be influenced by different follow-up policies of the centres. WIDER IMPLICATIONS OF THE FINDINGS The study reveals the high potential of ovarian tissue freezing and transplantation, but only if freezing is performed in younger women. The study suggests focus should be placed on the first and not on repeated transplantations. It also opens the discussion of whether transplantation should rather be performed by experienced centres. STUDY FUNDING/COMPETING INTEREST(S) No funding. No competing interests.
CRIS-Team WoS Importer:2022-11-04